2013
DOI: 10.1378/chest.12-2221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coexisting Pneumonia and End-stage Renal Disease on Pleural Fluid Analysis in Patients With Hydrostatic Pleural Effusion

Abstract: Background: In individual patients, especially those who are hospitalized, several conditions often coexist that may be responsible for the development of a pleural effusion and may affect the pleural fl uid analysis (PFA). The objective of this study was to investigate the effects of end-stage renal disease and pneumonia on PFA in patients with hydrostatic pleural effusion. Methods:In a retrospective analysis of 1,064 consecutive patients who underwent thoracentesis at a university hospital, cell counts and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In general population, the presentations of pleural effusion are predominantly determined by the underlying disease, and cardiac insufficiency maybe the uppermost factor [14]. In ESRD, the emergence of pleural effusion maybe also related to uremic pleurisy, infection, and even part of the proportion of unexplained reasons [12,15,16]. According to the pathophysiological theory, the decrease of RRF in dialysis patients leads to fluid overload, and the accumulation of a large number of toxins inhibits the function of serous cells, platelets and other coagulation factors, resulting in increased capillary permeability of visceral and parietal pleura.…”
Section: Discussionmentioning
confidence: 99%
“…In general population, the presentations of pleural effusion are predominantly determined by the underlying disease, and cardiac insufficiency maybe the uppermost factor [14]. In ESRD, the emergence of pleural effusion maybe also related to uremic pleurisy, infection, and even part of the proportion of unexplained reasons [12,15,16]. According to the pathophysiological theory, the decrease of RRF in dialysis patients leads to fluid overload, and the accumulation of a large number of toxins inhibits the function of serous cells, platelets and other coagulation factors, resulting in increased capillary permeability of visceral and parietal pleura.…”
Section: Discussionmentioning
confidence: 99%
“…One retrospective study reported that in patients with chronic heart failure and concomitant pneumonia, 8 of 30 effusions remained transudate according to Light’s criteria. 15 In this study, pneumonia was diagnosed based on the presence of systemic inflammation syndrome and respiratory symptoms, and patients with other complicated conditions were excluded. In our study, pneumonia was determined based on the patient’s admission diagnosis and image findings, which may explain the lower proportion of exudates in our study.…”
Section: Discussionmentioning
confidence: 99%